Peran NGOs (Non-Govermental Oganizations) Lingkungan dalam Mitigasi Banjir di Praha, Republik Ceko - Kurnia Novianti (Jurnal Kajian Wilayah, 2013)
Successful flood mitigation performed by the Czech Republic becomes an interesting issue for the author because it is relevant to current condition. Flood, in the authors observation, became a problem that seems unresolved until now. Often occur every time the rainy season and is considered a natural thing despite widespread impact. However, some literatures on flood mitigation in Prague some time ago showed interesting fact. People of Czech chose to friendly with the flood. By learning from them, the flood control by recognizing the causes and mobilize all society elements that exist to mitigate them to restrain broader impacts.This article aims to map the floods mitigation that been done by elements in society. Focusing on environmental NGOs, this article describes that cooperation between these elements do not always harmonize, there is different opinion even diverse activities. Background of values, ideologies and different interests led to various responses, roles and strategies. Using data from previous year of research and other secondary data, this article not only explores the phenomena of flooding in the city of Prague in particular, but also analyzes responses, roles and strategies undertaken by some environmental NGOs in actor-based approach perspective.Key words: floods mitigation, NGO, society, actor-based approach, The Czech Republic.